Highly efficient carbon dots and their nanohybrids for trichromatic white LEDs. Issue 22 (23rd May 2018) - Yuan, Biao; Xie, Zheng; Chen, Ping; Zhou, Shuyun
Abstract : Alkali-induced red-emitting carbon dots are combined with N -(2-aminoethyl)-3-aminopropyltrimethoxysilane-functionalized green-emitting CDs to make nanohybrids that can be potentially applied in trichromatic white LEDs. Abstract : Carbon dots (CDs) are hotspot materials in the lighting and display fields due to their low toxicity, high photostability and ease of functionalization. However, the development of white LEDs (WLEDs) is seriously restricted by the limited CDs with high photoluminescence quantum yield in the blue band and the absence of red-emitting CDs (R-CDs) with excellent photoluminescence intensity. In this work, we prepared alkali-induced R-CDs with quantum yields as high as 80%. The optical properties of the R-CDs are modulated by the alkali-induced surface electronic states. The R-CDs were doped into amino silane to realize highly efficient solid-state red luminescence. The R-CDs were combined with N -(2-aminoethyl)-3-aminopropyltrimethoxysilane-functionalized green-emitting CDs (G-SiCDs) with a quantum yield of 49% to fabricate G-SiCDs/R-CDs gel-glasses with tunable color gamut. The G-SiCDs/R-CDs nanohybrids showed excellent transmittance and thermal stability for use in WLEDs. A trichromatic warm WLED was built as a demonstration and displayed a luminous efficiency of 68.58 lm W −1 and a CRI of 90.2. These characteristics satisfy the requirements for indoor lighting.